2002
DOI: 10.1093/emboj/cdf414
|View full text |Cite
|
Sign up to set email alerts
|

Intramembrane proteolysis promotes trafficking of hepatitis C virus core protein to lipid droplets

Abstract: Hepatitis C virus (HCV) is the major causative pathogen associated with liver cirrhosis and hepatocellular carcinoma. The virus has a positive-sense RNA genome encoding a single polyprotein with the virion components located in the N-terminal portion. During biosynthesis of the polyprotein, an internal signal sequence between the core protein and the envelope protein E1 targets the nascent polypeptide to the endoplasmic reticulum (ER) membrane for translocation of E1 into the ER. Following membrane insertion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
454
0
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 430 publications
(470 citation statements)
references
References 44 publications
11
454
0
5
Order By: Relevance
“…Domain 2 was hypothesized to interact with lipid droplets and confer stability to the HCV core protein (12). Although a mutation in the signal sequence of core protein that renders it resistant to SPP proteolysis restored retention on lipid droplets and overall stability (30), deletion of domain 2 from HCV core protein leads to diffusion in the cytoplasm and degradation after processing by signal peptidase (30). Indeed, these data suggest that mature HCV core protein is retained on lipid droplets via domain 2, but they do not necessarily indicate that the region is required for the ER retention of HCV core protein.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Domain 2 was hypothesized to interact with lipid droplets and confer stability to the HCV core protein (12). Although a mutation in the signal sequence of core protein that renders it resistant to SPP proteolysis restored retention on lipid droplets and overall stability (30), deletion of domain 2 from HCV core protein leads to diffusion in the cytoplasm and degradation after processing by signal peptidase (30). Indeed, these data suggest that mature HCV core protein is retained on lipid droplets via domain 2, but they do not necessarily indicate that the region is required for the ER retention of HCV core protein.…”
Section: Discussionmentioning
confidence: 99%
“…Martoglio and colleagues reported that HCV core protein is processed by SPP after cleavage by host signal peptidase and that Ala 180 , Ser 183 , and Cys 184 residues in the signal sequence of HCV core protein of type 1a Glasgow strain are essential for SPP proteolysis, as they maintain the structure of the breaking ␣-helix (23,30). To determine the amino acids essential for SPP cleavage of the signal sequence of type 1b HCV core protein, Flag-Core-E1-HA and its substitution mutants were expressed in 293T cells (Fig.…”
Section: Region Required For Er Retention Of Hcv Core Proteinmentioning
confidence: 99%
See 2 more Smart Citations
“…Des études complémentaires ont montré que le clivage de la protéine de core par une protéase cellulaire, la SPP (signal peptide peptidase) ( Figure 1A et 1B) est nécessaire pour permettre la migration de cette protéine vers la surface des gouttelettes [9]. Après ce clivage, la protéine de core du VHC reste ancrée dans la membrane du RE ou associée aux gouttelettes grâce à la présence d'un domaine carboxy-terminal hydrophobe, sans équivalent dans la protéine de core des autres Flavivirus (à l'exception du virus GBV-B, très proche phylogénétiquement du VHC) [10].…”
Section: Interaction Entre Le Virus Et Les Gouttelettes Lipidiquesunclassified